Research on the Isolation Technology for Reverse Conducting IGCT - CHEN Fanglin; WU Yudong; ZHANG Ming; TANG Longgu; CHEN Yongmin; GAO Jianning (Kongzhi Yu Xinxi Jishu)
Isolation between GCT and FRD is the key technology in reverse conducting IGCT (RC_IGCT) developing. Compared with the existing isolation technology, a new method with compensated PNP isolation structure was proposed. Based on Silvaco simulation, process experiment and certification test were carried out on RC_GCTs wafers with 4 "and 6" substrates. The results show that the new method can increase the isolation voltage and reduce the difficulties both in the design and process.